A novel fabricated conductive substrate for enhancing the mass loading of NiCoLDH nanosheets for high areal specific capacity in hybrid supercapacitors. (1st February 2021) - Kang, Chenxia; Fang, Ju; Liu, Xi; Li, Shuxian; Wan, Shuyun; Fu, Likang; Liu, Qiming
Highlights: A novel conductive substrate (Ni3 S2 @NF) is fabricated by directly vulcanizing nickel foam. The Ni3 S2 @NF substrate possesses higher mass loading ability to active materials compared with pure nickel foam. NiCoLDH@Ni3 S2 @NF-480 heterostructure displays a specific capacity of 2.021 C cm −2 at 1 mA cm −2 . The hybrid supercapacitors exhibit a volumetric energy density of 0.52 mW h cm −3 . Abstract: Nickel foam (NF), as an excellent conductive substrate, is usually applied to the preparation of electrodes. However, the surface of nickel foam is too smooth to increase the loading of active materials. In this work, a facile method is developed to improve the mass loading of NiCo-layered double hydroxide nanosheets (NiCoLDH NSs) by directly vulcanizing nickel foam. The Ni3 S2 nanocone formed on the surface of nickel foam (Ni3 S2 @NF) is characterized by XRD, XPS and SEM. The obtained NiCoLDH@Ni3 S2 @NF-480 using Ni3 S2 @NF as substrate possesses high NiCoLDH areal mass loading of 4.0 mg cm −2, which is far above that of NiCoLDH@NF-480 using pure NF as substrate (0.2 mg cm −2 ). Accordingly, the NiCoLDH@Ni3 S2 @NF-480 electrode displays a high specific capacity of 2.021 C cm −2 under the current density of 1 mA cm −2 . It also presents excellent cycling stability with 92% of capacity retention after 5000 times cycles. The hybrid asymmetric supercapacitor (NiCoLDH@Ni3 S2 @NF-480//nitrogen-doped mesoporous carbon) exhibits a high volumetric energy density of 0.52 mW h cm −3 and high power density of 32 mW cm −3 . This work may provide a new substrate for fabricating the high mass loading electrode in energy storage device.